Patterns of gray matter alterations in migraine and restless legs syndrome. Issue 1 (12th November 2018) - Yang, Fu‐Chi; Chou, Kun‐Hsien; Lee, Pei‐Lin; Yin, Jiu‐Haw; Chen, Shao‐Yuan; Kao, Hung‐Wen; Sung, Yueh‐Feng; Chou, Chung‐Hsing; Tsai, Chia‐Kuang; Tsai, Chia‐Lin; Lin, Ching‐Po; Lee, Jiunn‐Tay
Abstract: Objectives: Migraine and restless legs syndrome (RLS) are often comorbid and share elements of pathology; however, their neuroanatomical underpinnings are poorly understood. This study aimed to identify patterns of gray matter volume (GMV) alteration specific to and common among patients with RLS, migraine, and comorbid migraine and RLS. Methods: High‐resolution T1‐weighted images were acquired from 116 subjects: 27 RLS patients, 22 migraine patients, 22 patients with comorbid migraine and RLS, and 45 healthy controls. Direct group comparisons and conjunction analysis were first used to localize the distinct and shared neural signatures of migraine and RLS. We also investigated whether the shared neural signature could be replicated in an additional comorbid migraine/RLS group. Results: Compared with healthy controls, migraine patients showed GMV changes in the lateral occipital cortex, cerebellum, frontal pole, and middle frontal gyrus (MFG), and RLS patients showed GMV changes in the thalamus, middle temporal gyrus, anterior cingulate cortex, insular cortex, and MFG. In migraine, compared with RLS, GMV differences were found in the precuneus, lateral occipital and occipital fusiform cortex, superior frontal and precentral gyri, and cerebellum. Conjunction analyses for these disorders showed altered GMV in the MFG, also found in patients with comorbid migraine and RLS. The GMV of the MFG also correlated with sleep quality in patients with comorbid migraine and RLS. Interpretation: Migraine and RLS are characterized by shared and distinctive neuroanatomical characteristics, with a specific role of the MFG. These findings may be related to shared pathophysiology of these two distinct disorders.